Self-perception of mental illness, and subjective and objective cognitive functioning in people with schizophrenia - Chuang SP (Dove Medical Press, 2019)
Shu Ping Chuang,1 Jo Yung Wei Wu,2,3 Chien Shu Wang41Department of Psychiatry, Zuoying Branch of Kaohsiung Armed Forces General Hospital, Kaohsiung, Taiwan; 2Department of Counseling and Guidance, National University of Tainan, Tainan, Taiwan; 3Good-Day Psychology Clinic, Tainan, Taiwan; 4Department of Psychiatry, Kaohsiung Armed Forces General Hospital, Kaohsiung, TaiwanBackground: People with schizophrenia may have a negative self-perception of mental illness. However, the relationship between the self-perception of illness and subjective and objective cognitive functioning remains unclear.Method: Thirty-seven people with schizophrenia were enrolled in the study group. All subjects completed self-reported self-perception of mental illness questionnaires (Birchwood Insight Scale [BIS], Internalized Stigma of Mental Illness [ISMI]), subjective cognitive functioning (Scale to Investigate Cognition in Schizophrenia [SSTICS]) and objective cognitive functioning (Luria Nebraska Neuropsychological Battery [LNNB]).Results: Spearman’s rank analysis showed that awareness of illness (domain of insight) was positively associated with most domains of SSTICS and ISMI. Total insight was positively correlated with alienation (domain of ISMI).  Need for treatment (domain of insight) was negatively correlated with stigma resistance (domain of ISMI). Awareness of symptoms (domain of insight) and total insight were negatively associated with receptive speech and arithmetic (LNNB subtest), respectively. ISMI was positively correlated with most domains of SSTICS, but not with LNNB. The group with good insight had higher scores in attention (domain of SSTICS) and total SSTICS and alienation, stereotype endorsement, social withdrawal (domains of ISMI) and total ISMI than the group with poor insight. The group with mild to moderate internalized stigma had higher scores in explicit memory, attention, language, praxia (domains of SSTICS) and total SSTICS than the group with no internalized stigma.Conclusion: We identified that awareness of illness (domain of insight), internalized stigma were significantly associated with most domains of SSTICS, but not with LNNB. Total insight and awareness of symptoms (domain of insight) were significantly associated with receptive speech and arithmetic (LNNB subtest), respectively. Schizophrenia with higher insight or more internalized stigma reported more subjective cognitive impairment. Future studies with larger samples involving follow up are necessary to verify our findings and extend the applicability.Keywords: self perception, insight, internalized stigma, Luria Nebraska neuropsychological battery, schizophrenia